Hedging entry and exit decisions: activating and deactivating barrier options. Issue 1 (2002) - Gauthier, Laurent
Abstract : Abstract. Investment projects and businesses can be entered or exited at a cost, and the theory of real option teaches us how to find optimal activity levels that should trigger entry or exit. However, in practice, different managers or owners operate under different constraints and might apply different thresholds to the same business. We are interested in the hedging of the risk related to the cost of sub-optimal entry or exit. We introduce a new class of derivative products that can hedge this risk. The pricing of these derivatives involves the joint law of a Brownian excursion and its supremum, which is calculated thanks to Bessel processes-related distribution laws.